Patient-Centered, Culturally Responsive Behavioral Economics Intervention to Optimize Retention in HIV Care - Vinita Sharma; Alida Gertz; Neille Saint-Cyr; Miguel Vasquez; Karen Wint; Marie-Jose Francois; Dinorah Martinez Tyson; Stephanie Marhefka; Phillip Phan; Harsha Thirumurthy; Miguel Reina Ortiz (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Behavioral economics is a field that optimizes decision-making by nudging people to a desired behavior. Interventions based on behavioral economics principles have been used to improve HIV outcomes. According to the CDC, culturally responsive methods have been used to adapt other types of HIV interventions. However, culturally responsive methods have not been used to adapt HIV-focused behavioral economics interventions. This study identifies patient-centered perspectives from both patients and providers regarding the culturally responsive development of behavioral economics-based interventions with incentives to optimize retention in care for HIV (RICH) among Latinos living with HIV (LLHIVs). HIV care providers and LLHIVs completed semistructured interviews. Interview guides were based on a modified version of the Ecological Validity and Cultural Sensitivity, a cultural responsiveness framework. Participants reported that monetary incentives, including nonrestrictive gift cards (i.e., not limited on where or what participants can purchase), would be acceptable. Participants noted, however, that LLHIVs continue their HIV care primarily for the benefit of their health and not for the sake of receiving incentives. Language preferences and careful wording were mentioned as important considerations. Perceived stigma and discrimination about HIV status were reported as barriers to LLHIVs participating in such interventions. These findings suggest that behavioral economics-based interventions to engage LLHIVs in optimizing RICH are feasible. Cultural responsiveness can be leveraged to increase the acceptability of such interventions. Additional research is needed to evaluate the real-world effectiveness of culturally responsive behavioral economics-based interventions in optimizing RICH and other HIV-related outcomes among LLHIVs and other key population groups.